Functional neurological (conversion) symptoms mediate the effect of self-stigma in women seeking psychological help on their psychological well-being (Annals of Medical Research, 2025)
Aim: This study aimed to examine the effect of self-stigma of seeking psychological help on psychological well-being in patients diagnosed with functional neurological symptom disorder (formerly conversion disorder) through conversion symptoms.Materials and Methods: In this cross-sectional study, the Self-Stigma of Seeking Psychological Help Scale (SSPHS), Psychological Well-Being Scale (PWBS), and Somatoform Dissociation Questionnaire (SDQ-20) were administered to the FNSD and HC groups.Results: The FNSD group consisting of 31 females (12 motor (M)-FNSD, 9 somatosensory (SS)-FNSD, and 10 mixed-FNSD) and the HC group consisting of 32 females were similar in terms of age (p = 0.350), education level (p = 0.386), marital status (p = 0.579), and working status (p = 0.136). Significant differences were observed between the FNSD and HC groups in terms of SSPHS (p
Keywords: Functional neurological symptom disorder; Conversion disorder; Psychological well-being; Self-stigma; Mediation analysis